The Importance of Improving Service Quality for Customer Satisfaction: A Case Study of Bank Muamalat in Bogor City - Eka Rofiyanti; Avradya Mayagita; Charles Magwari Omboto; Nataya Premchaporn (Ilomata International Journal of Social Science, 2022)
The development of the banking world in Indonesia is marked by one of them is the establishment of Islamic banks. Islamic banks are banks that operate by not relying on bank interest. With a population that is 80% Muslim, Islamic banks are predicted to have very good prospects in the future. However, the current fact is that there are still many customer complaints related to the quality of service at Islamic banks. This study aims to answer the questions on how the service quality of Bank Muamalat Bogor and how the customer satisfaction is perceived by customers of Bank Muamalat Bogor. The data collection technique was carried out by participant observation and semi-structured interviews since this type of interview is more flexible in which questions can be adapted and changed depending on the answers of the informants. For this study, researchers interviewed 15 bank customers. The results of this study indicate that of the 5 dimensions of service quality, 3 of them received negative responses from customers, namely reliability, assurance and tangible. However, apart from the negative responses, Bank Muamalat with a sharia basis also received a positive assessment for the dimensions of responsiveness and empathy in which customers are satisfied with the services provided by friendly and patient staff who have a high sense of empathy. However, the friendliness and kindness of the staff only is not sufficient. To be able to compete with other commercial banks, Bank Muamalat must be able to improve the quality of its services from all the 5 dimensions of service quality